Discovery Learning Model with Animation Based Media on Social Studies Learning Motivation for 5th Grade Students of Elementary School - Darmawati D; Muhammad Nawir; Hidayah Quraisy (Indonesian Journal of Primary Education, 2022)
Lack of motivation to learn social studies in 5th grade students of SD Inpres Tattakang, so students are less interested and play a lot when learning takes place. The purpose of this study was to determine the effect of the animated media-based Discovery Learning Model on the social studies learning motivation of 5th grade students of SD Inpres Tattakang Pallangga. This type of research is a quasi-experimental non-equivalent control group design experiment. The sampling technique used random sampling. The sample in this study was class 5a which amounted to 27 people as the control class and class 5b which amounted to 28 people as the experimental class. This type of data collection uses a motivational questionnaire to measure learning motivation. The data analysis technique used is the Manova test, which was previously tested for normality and homogeneity. The results of this study showed an increase in social studies learning motivation, the results of the motivation questionnaire Manova test obtained a sig value. 0.00 0.05 (smaller than 0.05) with a 95% confidence level, Ho is rejected and Ha is accepted, meaning that there is an influence of the animated media-based Discovery Learning Modelon the learning motivation of 5th graders at SD Inpres Tattakang Pallangga. So, it can be concluded that the learning model of Discovery Learning based on animation media has an influence on the social studies learning motivation of the 5th grade students of SD Inpres Tattakang.